ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN E-COMMERCE (Studi pada Perusahaan yang Tergabung dalam Jakarta Islamic Index (JII) di Bursa Efek Indonesia) - Tania Dian Nugraini; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine whether there are differences in financial performance between companies included in the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange before and after the implementation of e-commerce. The data analysis technique used in this research is the sample T-test for data that is normally distributed. The variables analyzed consisted of the profitability ratio proxied by Return On Assets (ROA); liquidity ratio proxied by Current Ratio (CR); solvability ratio proxied by Debt to Assets Ratio (DAR); and activity ratio proxied by Total Assets Turnover (TATO). Based on the results of this study, the criteria for ROA, CR, DAR and TATO showed significant differences before and after the implementation of e-commerce.Keywords: Financial Performance, E-commerce, ROA, CR, DAR, TATO.